Analysis The Effect of Compensation and Work Environment on Cleaning Workers Performance With Work Motivation and Work Satisfaction as Mediating Variables in Swakelola Office Bukit Pelangi East Kutai - Handoko, Wiki Agus Tri; Rekarti, Endi; Safitri, Julia (Indonesian Journal of Advanced Research, 2024)
This study examines the impact of compensation and work environment on cleaning workers performance, with work motivation and job satisfaction as mediators. Using a quantitative survey method with 100 respondents, data were analyzed through Structural Equation Modeling Partial Least Square (SEM-PLS). The findings reveal that compensation does not affect performance but significantly influences work motivation, which, in turn, improves performance. Compensation impacts performance when mediated by work motivation. The work environment significantly affects performance and job satisfaction, while job satisfaction does not influence performance or mediate the relationship between the of work environment and performance.